Perioperative Assessment of Cerebral Oxygen Metabolism in Infants With Functionally Univentricular Hearts Undergoing the Bidirectional Cavopulmonary Connection. Issue 10 (October 2019) - Neunhoeffer, Felix; Michel, Jörg; Nehls, Wilma; Marx, Milena; Mustafi, Migdat; Magunia, Harry; Schuhmann, Martin; Schlensak, Christian; Hofbeck, Michael
Abstract : Objectives: The transition from single-ventricle lesions with surgically placed systemic-to-pulmonary artery shunt to the circulation following a bidirectional cavopulmonary connection results in higher pressure in the superior vena cava when compared with the preceding circulation. The aim of this study was to evaluate the impact of this transition on the perioperative cerebral oxygen metabolism. Design: Prospective observational cohort study. Setting: Pediatric critical care unit of a tertiary referral center. Patients: Sixteen infants after bidirectional cavopulmonary connection. Intervention: Cardiac surgery (bidirectional cavopulmonary connection). Measurements and Main Results: We measured regional cerebral oxygen saturation, amount of hemoglobin, blood flow velocity, and microperfusion immediately before, 12–24 hours, and 36–48 hours following bidirectional cavopulmonary connection. Based on these measurements, we calculated cerebral fractional tissue oxygen extraction and approximated cerebral metabolic rate of oxygen. Mean pressure in the superior vena cava increased significantly (8 vs 17 mm Hg; p < 0.001) following bidirectional cavopulmonary connection. Mean cerebral oxygen saturation increased from 49.0% (27.4–61.0) to 56.9% (39.5–64.0) ( p = 0.008), whereas mean cerebral blood flow velocity decreased from 80.0 arbitrary units (61.9–93.0) to 67.3 arbitrary units (59.0–83.3) ( p < 0.001). No change was found in the cerebral amount of hemoglobin and in the cerebral microperfusion. Mean cerebral fractional tissue oxygen extraction (0.48 [0.17–0.63] vs 0.30 [0.19–0.56]; p = 0.006) and approximated cerebral metabolic rate of oxygen (5.82 arbitrary units [2.70–8.78] vs 2.27 arbitrary units [1.19–7.35]; p < 0.001) decreased significantly. Conclusions: Establishment of bidirectional cavopulmonary connection is associated with postoperative improvement in cerebral oxygen metabolism. Cerebral amount of hemoglobin did not increase, although creation of the bidirectional cavopulmonary connection results in significant elevation in superior vena cava pressure. Improvement in cerebral oxygen metabolism was due to lower cerebral blood flow velocity and stable microperfusion, which may indicate intact cerebral autoregulation. Abstract : Supplemental Digital Content is available in the text.